The Role, Power and Influence of Company Chairs - Pettigrew, A; McNulty, T; Jobome, G; Morris, C (2011)
This paper develops an analytical framework to depict the heterogeneity that characterises the role of board chair and demonstrate the potential variability in how chairs operate boards and exercise power and influence on strategy, control and resource related tasks at board level. Theories of power and influence, as applied to top management teams and boards of directors, are explicated within the context of contemporary governance practices that are establishing the role of the board chair as distinct to that of the chief executive officer. Specifically, the paper maps sources of power and varying contemporary chair practices, including chair nomenclature (i.e. executive vs. non-executive chairs), chair origin (insider vs. outsider) and chair time (full-time vs. part-time). A number of theoretical chair-power models emerge from this analysis and are subject to empirical analysis using data collected from 160 chairs of 500 FTSE-listed companies. Theoretically and empirically, the paper complements structural approaches to studying boards with attention to behaviour on boards. By linking board structure, board process and the exercise of influence, the study reveals both differences amongst chairs in how they run the board, but also that chairs' differ in the influence they exert on board-related tasks. Full-time executive chairs exert their greatest influence in strategy and resource dependence tasks whereas part-time, non-executive chairs seem to exert more influence over monitoring and control tasks.